KONTRIBUSI NILAI BUKU DAN PENDAPATAN DALAM MENAMBAH RELEVANSI NILAI LABA - Zacharias, Jems Arison; Wirama, Dewa Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2016)
Th e aims of this research are to reveal the contribution of book value and revenue in adding the value relevance of earnings. Value relevance of earnings in this study was measured by the explanatory power (adjusted R 2 ) from the regression model between earnings and stock returns. The population in this study is taken from public companies listed on the Indonesian Stock Exchange from 2009-2011. Selection method of the sample was simple random sampling. T he data analysis was performed using the descriptive statistics, classical assumption test, simple linear regression and multiple linear regression. T he results of this research are that (1) b ook value contributed in increasing value relevance of earnings , (2) r evenue contributed in increasing value relevance of earnings , (3) and t he additional value relevance of earnings from revenue is greater than that of the book value.
Keywords: Value Relevance, Book Value, Revenue